Influence of coal mining on the lower Yellow River region and related management countermeasures-- Taking Heze mining area as an example - Li Xinghua; Zhang Qi; Liu Zhaoping; Yan Jianchi; Zhang kai (MATEC Web of Conferences, 2022)
To realize the ecological protection and high-quality development of the Yellow River basin is related to the centenary project of the Chinese nation. The middle and lower reaches of the Yellow River are rich in coal resources and have a long history of mining. Large-scale coal mining activities lead to the destruction of underground aquifer, surface subsidence and the reduction of cultivated land, which seriously threatens the safety of local ecological environment, land resources and water resources. Luxi coal base Heze mining area, for example, the analysis of coal mining activities and land resources, ecological environment, the contradiction between water resources protection and its causes, and put forward preventive measures, to help alleviate the lower Yellow River coal mining and land resources, ecological environment, water resources protection, to realize luxi mining area and the lower Yellow River ecological environment protection and high quality development is of great significance.